Bonding performance of universal adhesives in different etching modes - Wagner, Anna; Wendler, Michael; Petschelt, Anselm; Belli, Renan; Lohbauer, Ulrich (Journal of Dentistry, 2014)
The aim of this study was to compare the microtensile bond strength (?TBS) and resin penetration into dentine of three universal adhesives (UAs) applied in two different etching modes (i.e. self-etch or etch-and-rinse). The effect of thermocycling on the ?TBS was also evaluated.The occlusal third of sound human molars was removed and the exposed surfaces were treated with three UAs (Futurabond Universal, Scotchbond Universal Adhesive and All-Bond Universal) in self-etch or etch-and-rinse mode. Two one-step self-etch adhesives (Futurabond DC and Futurabond M) were applied on additional teeth as reference. After composite build up, the specimens were stored for 24 h in distilled water at 37 °C or thermocycled for 5000 cycles. Composite/dentine beams were prepared (1 mm(2)) and ?TBS test was performed. Data was analyzed using three-way ANOVA and Tukey's test (?=0.05). One additional tooth was prepared for each group for evaluation of infiltration ability into dentine by dyeing the adhesives with a fluorochrome (Rhodamine B). After longitudinal sectioning, the generated interfaces were examined under confocal laser scanning microscopy.The addition of an etching step did not significantly affect the ?TBS of none of the UAs, when compared to their self-etch application mode. All pre-etched specimens showed considerably longer resin tags and thicker hybrid layers. Thermocycling had no significant effect on the ?TBS of the UAs.Application of an etching step prior to UAs improves their dentine penetration, but does not affect their bond strength to dentine after 24h or after thermocycling for 5000 cycles.Similar bond strength values were observed for the UAs regardless of application mode, which makes them reliable for working under different clinical conditions.
EVALuna2:24659